Lycra splinting garments for adults with intellectual disabilities who fall due to gait or balance issues: a feasibility study. Issue 5 (14th February 2018) - Finlayson, J.; Crockett, J.; Shanmugam, S.; Stansfield, B.
Abstract: Background: Adults with intellectual disabilities (IDs) experience high rates of falls and have high rates of gait or balance issues which contribute to falls. Lycra splinting garments (LSGs) have potential to improve gait or balance, but they have never before been tested with adults with IDs who fall due to gait or balance issues. The aim of this study was to test in adults with IDs, the feasibility of using LSGs to improve movement and function and reduce falls, whilst also exploring usability and likely compliance. Method: A convenience sample of nine adults with IDs wore tailored LSGs over a 6‐week assessment period. Laboratory‐based foot clearance, balance, and gait measures were collected pre‐ and post‐LSG‐wear. Falls charts and questionnaires on usability and likely compliance were also completed. Results: Seven participants experienced a reduction in falls during their six weeks of LSG wear; most notably in the group of five participants who wore lycra splinting socks, compared with only two in the group of four who wore lycra splinting shorts or leggings only. Conclusion: Lycra splinting socks are likely to bring about positive outcomes for adults with IDs who fall due to gait/balance issues on an individual case by case basis over time, but further research is required to test this hypothesis under randomised controlled trial conditions. Potential benefits of more intrusive LSGs are outweighed by reported problems with usability and compliance.